(3efgL GdSGdc Edi CdajI GHf eGdcs - (3fhQ GdOjf CHh Gd MSf Ydj Hf eMeO Hf YjSi GdCTehfis; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3GHQGgje Hf GdMGL Ydi GdCMOH s)
(3ChdgG (B:s
(3bGd GdTjN GdCTehfi GdTGaYi QVi Gddg Yfg CeG HYO MeO Gddg Ydi eG efM ef CSHGH GdHjGf , agPG TQM dWja HOjY Ydi CdajI GHf eGdc egPH GdebGUO hGVM GdeSGdc hbO dbHJg efgL GdSGdc Edi Cdajg GHf eGdc s
(3BNQgG (B:s
(3aCMeO Gddg eUdjkG Ydi NjQ fHi CQSdkG hBdg GdZQ GdcQGe GdHQQg hUMHg GdefJLHjf GdNjQg hGdMeO ddg ChdkG hBNQkG hHGWfkG hXGgQkG hUdi Gddg Ydi SjOfG eMeO Edi jhe GdOjf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs